Загальнонародна та рідкісна діалектна лексика ХIХ ст. у мові першодруків творів П. О. Куліша - Кумеда, О.П. (Лексикографічний бюлетень, 2013)
In article on a material lifetime primary sources and in a support on P. Kulish’s local dialect environment lexical features in his language are considered; their genesis in a context of eastern Polissia dialect is found out; also orientation of the author the broad audience eastern Ukrainians dialects is proved. Further inquiry on language of Kulish’s first printings will make it possible to create an integral work about idiolect of the writer and to identify its role in development of new Ukrainian literary language.